2022
DOI: 10.3390/jpm12101634
|View full text |Cite
|
Sign up to set email alerts
|

Association between Gut Microbiota and Emotional-Behavioral Symptoms in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: Previous studies have explored the role of the microbiome in attention-deficit/hyperactivity disorder (ADHD). However, whether the microbiome is correlated with emotional–behavioral disturbances, the most common comorbid symptom of ADHD, remains unclear. We established a cross-sectional study in which 6- to 18-year-old children with ADHD who were receiving no medication and a healthy control group of children without ADHD were recruited to analyze their microbiome composition. Microbiota of fecal samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…Interestingly, a recent cross-sectional study investigated the bacterial strains in the gut microbiome of 54 children affected by ADHD compared to 22 HC and found that the concentrations of the bacterial strains were positively associated with emotional-behavioural symptoms which could result from (or express) ED. (334). In particular, Rhuminococcus was positively correlated with externalizing symptoms (i.e., rule-breaking behaviour) and Agathobacter with internalizing symptoms (i.e., depressive symptoms and withdrawal).…”
Section: Inflammation Emotion Dysregulation and Gut-brain Axis Abnorm...mentioning
confidence: 87%
See 1 more Smart Citation
“…Interestingly, a recent cross-sectional study investigated the bacterial strains in the gut microbiome of 54 children affected by ADHD compared to 22 HC and found that the concentrations of the bacterial strains were positively associated with emotional-behavioural symptoms which could result from (or express) ED. (334). In particular, Rhuminococcus was positively correlated with externalizing symptoms (i.e., rule-breaking behaviour) and Agathobacter with internalizing symptoms (i.e., depressive symptoms and withdrawal).…”
Section: Inflammation Emotion Dysregulation and Gut-brain Axis Abnorm...mentioning
confidence: 87%
“…Like other neuropsychiatric illnesses, ADHD has high comorbidity with gastrointestinal disturbances, such as constipation and abdominal pain (331,332), and diseases, such as ulcerative colitis (333). Some works have also reported discrepancies between ADHD and HC in the microbiome variability (334)(335)(336), which could be associated with distinct proinflammatory profiles and ADHD symptoms (337,338), although results are still inconclusive (339).…”
Section: Inflammation Emotion Dysregulation and Gut-brain Axis Abnorm...mentioning
confidence: 99%
“…Consistent with previous studies, we found that the genus Roseburia and genus Desulfovibrio were associated with ADHD. Lee et al (2022) conducted a cross-sectional study that compared the composition of the gut microbiome in 54 drug-naive children with ADHD and 22 healthy controls, and found that the abundance of the phylum Proteobacteria and the genera Roseburia , Agathobacter , Phascolarctobacterium , Prevotella_2 , Acidaminococcus , and the Ruminococcus gnavus group were increased in the ADHD group compared to the healthy controls. Our study confirms that the increase in genus Roseburia abundance is caused by ADHD, but the underlying mechanism remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the general composition of the microbiota, while some individual studies have found differences in patients with ADHD in diversity indices (alpha and beta) [ 167 , 168 ], the overall evidence and meta-analyses point to high heterogeneity across studies and do not support a consistent association of diversity indices with ADHD [ 160 , 166 ]. In general, the studies evaluating the microbiota effects on ADHD are limited, and contradictory/inconsistent findings have been reported, likely due to methodological differences and small sample sizes [ 157 ].…”
Section: Metagenomicsmentioning
confidence: 99%